Some Approximation Properties of Szasz–Mirakyan–Bernstein Operators of the Chlodovsky Type - Simsek, E.; Tunç, E. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We motivate a new sequence of positive linear operators by means of the Chlodovsky-type Szasz–Mirakyan–Bernstein operators and investigate some approximation properties of these operators in the space of continuous functions defined on the right semiaxis. We also find the order of this approximation by using the modulus of continuity and present the Voronovskaya-type theorem.